ANALISIS PERUBAHAN TUTUPAN LAHAN DI SUB DAS TOILI KABUPATEN BANGGAI - Muhammad Adam Suni; Syukur Asa; Fahrul Himalaya Umar; Rhamdhani Fitrah Baharuddin (Yayasan Nusantara Hasana Berdikari, 2023)
Land conversion or land cover cange is a change in the function of part or all of a land area from its original function (according to plan) to another function that causes negative impacts (problems) on the environment and the potential of the land itself. The research aims to analyze changes in land cover over a period of ten years with Landsat 8 imagery in 2013 and 2022 and to analyze changes in land cover in the Toili sub-basin, Banggai Regency. This study uses guided image analysis (supervised). Land cover classes in the Toili sub-watershed are divided into 9 (nine) land cover classes, namely, secondary dryland forest, settlements, plantations, dryland agriculture, paddy fields, shrubs, open land, bodies of water, and clouds. From the test of accuracy or precision of the results of loss of satellite imagery with the guided classification method (Supervised) has an accuracy level of 88.54%. The results of the analysis show that the largest increase in area is in the plantation class while the largest decrease in area is in the dry land farming class, this is the impact of activities carried out by the local community.